Makro- i mikrootoczenie banków komercyjnych w Polsce – główne tendencje i czynniki - Pettersen-Sobczyk, Monika (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The text analyses macro- and microenvironment of commercial banks in Polandin order to evaluate their position vis-à-vis banks in other European states. AlthoughPolish banking system is not as developed as the banking systems of other Europeanstates, the situation is changing substantially and the differences diminish.